Preliminary comparative serological evaluation of Histamine H2 receptors in dogs with an acute onset of vomiting treated with Ranitidine and healthy dogs. (December 2020) - Bottero, E.; Benvenuti, E.; Ferriani, R.; Manassero, E.; Re, G.; Barbero, R.
Highlights: Ranitidine (RT) is an antagonist against H2 histamine receptors (H2R) that weakly suppress acid secretion in patients. Despite that a clinical effect is often achieved. H2 antagonists (H2RA) also called H2 blockers, are a group of medications that block the action of histamine at the H2R of parietal cells in the stomach. Preliminary analysis indicates that the levels of H2 receptors in the serum and gastric walls are the same. Evidence suggests that the level of H2 receptors in dogs with acute vomiting is greater than in healthy dogs, thus probably contributing to a greater efficiency of ranitidine treatment. Abstract: Despite the lack of evidence of the ability to suppress gastric acid secretion in dogs, ranitidine (RT) is often used to control clinical signs in dogs with acute vomiting even if the way it happens it is still largely unknown. The aim of this study was thus to evaluate the therapeutic effect of ranitidine on H2 receptors in dogs with acute vomiting. To investigate the RT activity a preliminary study was performed in dogs which underwent gastroscopy analyses, demonstrating that the level of H2R observed in the serum and gastric wall tissue was the same [1.473(1.30; 1.79) ng/ml and 1.498 (1.33; 1.85) ng/ml, respectively]. After that H2R levels in the serum of 22 healthy dogs (Group 1) and in a group of 22 dogs with acute vomiting (Group 2) were compared both before (T0), after 7–10 days (T1) of 2 mg/kg twice a day ranitidine administration and after 11 days since the drug was discontinued (T2). Significant differences ( p <0.001) were detected between the level of circulating H2R among Group 1: 0.41 ng/ml (0.28;0.54) and Group 2: 2.27 ng/ml (2.11;2.49) at T0. In Group 2, no difference in the level of H2R was detected in samples collected at T0 compared to those at T1 [T1: 2.32 ng/ml (2.14; 2.49)] and T2 [T2: 2.30 ng/ml (1.99;2.69)]. In Group 2 all patients but one displayed remission of symptoms attributable to inflammatory gastropathy at the first withdrawal (T1: 7–10 days), while at the second withdrawal (T2: after 21 days), remission was detected in all dogs. Our preliminary hypothesis is that the clinical efficacy of ranitidine is related to the greater expression of H2 receptors in patients with acute vomiting. This increased expression may be due to continuous pathological stimulus at the gastric level. Further studies with a wider population are needed to better investigate the activity of RT in dogs with acute onset of vomiting.